An experimental evidence by using f-score in Predicting fraud, errors in financial statements of Listed companies in vietnam - Trinh, Thu Ngan (2020)
The study determines the effect of F-score to detect frauds and errors in listed companies in Vietnam and some factors which impact to misstatement in financial reports. The author uses accounting data of financial statement from 2015-2017 in 156 misstated listed companies in Vietnam. In conclusion, the author suggests that F-score is not useful tool in Vietnam market and only one soft asset variable has negative relationship with real misstatement value statistically in financial statements.